The Development of Peanut Production in Turkey and Osmaniye - Nermin BAHŞİ and Dilek BOSTAN BUDAK (Archives of Current Research International, 2024)
Peanuts are very important nutrition not only for human beings but also animals because of its rich content. Peanut plays a crucial role in the economy of Osmaniye province in Turkey. In 2012, peanuts were registered as a geographically indicated product of Osmaniye by the Turkish Patent and Trademark Office. This study examines current state of peanut production in Turkey and Osmaniye from 2004 to 2023. Over the past 20 years, peanut cultivation areas have expanded in Osmaniye, leading to increase in the share of peanut farming within cereals and other crops from about 7% in 2004 to approximately 12% in 2023. While Osmaniye held the largest share of peanut cultivation areas at 39% in 2004, this decreased to 25% by 2023. During this period, Adana emerged as a major peanut producing province, holding 45% of the cultivation share. The considerable expansion of peanut farming in Adana led to decline is Omaniye’s position in producing rankings. Additionally, the number of provinces involved in peanut farming has increased, indicating a broader geographical distribution and diversification of peanut agriculture across the country. There is a need for an organization that can support producers with affordable input supplies, market access, dissemination of innovation, and storage solutions, fostering unity and collaboration within the sector. Expanding the range of peanut based products beyond snacks could open new market opportunities for producers, stabilize market prices, and held reduce income disparities.